Science and Technology for Alen-Alen Entrepreneur Comunities - Sinaga, Hotnida; Lubis, Linda Masniary; Nasution, Siti Kadijah (Talenta Publisher Universitas Sumatera Utara, 2018)
This community service activity was intended to assist entrepreneurs engaged in the production of alen-alen, a product made from cassava. There are some problems encountered in the production process, such as washing raw materials manually, work safety during the production practice, products that are not in accordance with standard hygiene and sanitation and packaging process that has not been designed properly. The entrepreneurs want to increase production but the equipment and processing machinery are very limited. To overcome this problem, several methods can be performed by the academics, such as facilitating them with appropriate tools that meet the needs in the field. A cassava washer unit and specific boiler tools to avoid hot steam when taking the material were offered. In addition, entrepreneurs were trained in hygiene and sanitation in alen-alen making, educated for packaging technology quality, raw material selection and the use of food coloring, formulating variations for alen-alen manufacture, as well as financial bookkeeping training. The implementation of these activities is expected to generate shorter production process time leading to further increase in the production, income and welfare of the entrepreneurs.